Characterization of Bacteriophage vB-EcoS-95, Isolated From Urban Sewage and Revealing Extremely Rapid Lytic Development - Topka, Gracja; Bloch, Sylwia; Nejman-Faleńczyk, Bożena; Gąsior, Tomasz; Jurczak-Kurek, Agata; Necel, Agnieszka; Dydecka, Aleksandra; Richert, Malwina; Węgrzyn, Grzegorz; Węgrzyn, Alicja (Frontiers in Microbiology, 2019)
Morphological, biological and genetic characteristics of a virulent Siphoviridae phage, named vB-EcoS-95, is reported. This phage was isolated from urban sewage. It was found to infect some Escherichia coli strains giving clear plaques. The genome of this phage is composed of 50,910 bp and contains 89 ORFs. Importantly, none of the predicted ORFs shows any similarity with known pathogenic factors that would prevent its use in medicine. Genome sequence analysis of vB-EcoS-95 revealed 74% similarity to genomic sequence of Shigella phage pSf-1. Compared to pSf-1, phage vb-EcoS-95 does not infect Shigella strains and has an efficient bacteriolytic activity against some E. coli strains. One-step growth analysis revealed that this phage has a very short latent period (4 min), and average burst size of 115 plaque forming units per cell, which points to its high infectivity of host cells and strong lytic activity. The bacteriolytic effect of vB-EcoS-95 was tested also on biofilm-producing strains. These results indicate that vB-EcoS-95 is a newly discovered E. coli phage that may be potentially used to control the formation of biofilms.